Aldosterone-Mineralocorticoid Receptor Cell Biology to Translational Medicine - Harvey, Brian; Jaisser, Frederic (IntechOpen, 2019)
This book is an open access dissemination of the EU COST Action ADMIRE in Aldosterone/Mineralocorticoid Receptor (MR) physiology and pathophysiology. Aldosterone is the major hormone regulating blood pressure. Alterations in blood levels of aldosterone and genetic mutations in the MR receptor are major causes of hypertension and comorbidities. Many of the drugs in clinical use, and in development for treating hypertension, target aldosterone and MR actions in the kidney and cardiovascular system. The ADMIRE book assembles review chapters from 16 European ADMIRE laboratories providing the latest insights into mechanisms of aldosterone synthesis/secretion, aldosterone/MR physiology and signaling, and the pathophysiological roles of aldosterone/MR activation.